The Role of Women in Preserving Banjar's Specialty Food Jaring Tahilala - Ramiadani, Ayu Kesuma; Ilhami, M. Ridha; Rusmaniah, Rusmaniah; Rahmia, Sovia Husni; Triyono, Sigit (Program Studi Pendidikan IPS, 2026)
Technological advancements have influenced people’s lifestyles, including their food consumption patterns. Traditional foods that were once consumed across generations are now becoming marginalized, especially among the younger generation who tend to prefer fast food. Yet, traditional cuisine holds historical, philosophical, and cultural value. This study aims to describe the role of women in preserving a traditional Banjar food known as Jaring Tahilala. The research employs a qualitative approach using in-depth interviews and direct observation. The findings reveal that women play a role in sociocultural aspects, such as passing on knowledge to younger generations and maintaining good relationships with customers; in economic aspects, through marketing efforts and contributing to family income; and in technological aspects, by participating in production training. The conclusion of this study highlights that the preservation of Jaring Tahilala represents a concrete effort to uphold the cultural identity of the Banjar community amidst changing times.